Lipoxygenase-derived oxylipins are enriched in anti-citrullinated protein antibody (ACPA)-positive individuals at risk for developing rheumatoid arthritis - Liam J. O’Neil; Vidyanand Anaparti; Tanja Winter; Irene Smolik; Xiaobo Meng; Harold M. Aukema; Hani El-Gabalawy (Arthritis Research & Therapy, 2024)
Abstract Background Rheumatoid arthritis (RA) is typically preceded by an extended preclinical period where circulating autoantibodies, particularly anti-citrullinated protein antibodies (ACPA), are detectable in the absence of clinical arthritis. Increased dietary intake of anti-inflammatory omega-3 (ω3) polyunsaturated fatty acids (PUFA) has been shown to be associated with a lower the risk of developing incident RA in large epidemiological studies. It is currently not known how changes in fatty acid (FA) metabolism may impact on the progression towards RA in at-risk individuals. To begin to address this question, we profiled serum FAs and oxylipins in an established cohort of at-risk ACPA-positive first-degree relatives (FDR) of RA patients (N = 31), some of whom developed RA (N = 4), and compared their profile to ACPA-negative FDR from the same population (N = 10). Methods Gas chromatography (GC) was used for FA quantitation. Oxylipins were extracted and quantified using high-performance liquid chromatography–tandem mass spectrometry (HPLC/MS/MS). Results Although we did not detect any meaningful differences in overall FA content between ACPA + and ACPA − FDR, the levels of oxylipins derived from FA metabolism demonstrated significant differences between the two groups, with the ACPA + group demonstrating enrichment in circulating arachidonic acid- and eicosapentaenoic acid-derived molecules. Compared with the ACPA − FDR group, the ACPA + FDR, including those who progressed into inflammatory arthritis, displayed higher levels of LOX-derived oxylipins. Conclusion ACPA seropositivity in otherwise unaffected individuals at-risk for developing future RA based on family history (FDR) is associated with alterations in the serum oxylipin profile that suggests dysregulated LOX activity.